Digital Technology in Improving Tuberculosis Treatment Adherence: A Systematic Review - Amirah Jasmine; Annisa Nurul Husna; Safira Kamal (Faculty of Medicine Universitas Airlangga, 2026)
Introduction: Indonesia ranks second globally in the number of tuberculosis (TB) cases. One strategy to eliminate TB is to use research and technology. The long duration of treatment may lead to non-adherence. Digital health interventions have become a promising option for monitoring treatment adherence. This review aimed to evaluate how digital technology interventions can improve treatment adherence in TB. Methods: A systematic review was conducted by identifying primary data articles published on online platforms by using specific keywords. The sample size was determined in accordance with the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. All data were then systematically assessed and reviewed. Results: Of the 14 included studies, 13 found that digital technology led to high adherence to TB medication, while 1 found no link between usability and medication adherence. The intervention arm reached 99 % (pill dispenser) in adherence, and the lowest was 71.1 % (video-observed therapy). Conclusion: Digital technology intervention still has some obstacles despite promising outcomes. The limitations are poor internet connectivity, mobile phone ownership, and inferior-quality phones. This review could not assess the degree of adherence alteration, as the included studies showed adherence only at the end of the study. In addition, 4 of the 14 studies were categorized as having some concerns based on the risk of bias tool. Further studies are needed to assess how digital technology influences adherence to TB medication.